Looking Glass Self dalam Membentuk Citra Tubuh Menarik (Fenomena Lepas Pasang Jilbab) - Enjella, Nadia; Damaiyanti, Varinia Pura (Huma: Jurnal Sosiologi, 2025)
The shifting meaning of the hijab from a symbol of religiosity to a part of lifestyle and identity expression has given rise to the phenomenon of removing and re-wearing the hijab, which in turn sparks debates and new perspectives within society. This study aims to explore how female university students construct their self-concept leading to the practice of removing and re-wearing the hijab, as well as how they adapt to their social environment. Using a qualitative approach with phenomenological methods, data were collected through non-participatory observation, semi-structured interviews, and documentation. The findings reveal that students’ self-concept is shaped by a combination of personal values, physical comfort, aesthetic perception, and social norms. In practice, they adjust their appearance according to context: maintaining neatness in formal events, dressing more casually in peer groups, and constructing a certain image on social media. Social pressures emerge not only from direct interactions in their surroundings but also from comments and judgments in digital spaces. Employing Cooley’s Looking Glass Self theory, the study shows that others’ perceptions serve as a mirror that influences how students evaluate themselves and determine their appearance choices. This research contributes to sociological discussions on the dynamics of religious identity, social pressure in public spaces, and the negotiation of Muslim women’s identities within modernity. Further research is recommended to examine the phenomenon of hijab removal and re-wearing through a gender perspective, employing gender performativity theory.